KONTINUITAS DAN PERUBAHAN BENTUK SERTA MAKNA LAGU KEBANGSAAN INDONESIA RAYA - Mintargo, Wisnu; Soedarsono, R.M; Ganap, Victor (Institut Seni Indonesia Padang Panjang, 2012)
The main obyective of this paper is to analyze function of the song of Indonesian strugle in connection to the Indonesian independence from 1945 to 1949 viewed from the perspective of history. Through this analysis we hope that the process of history in the past can be reconstructed, especialy the history of music development in Indonesia; the background of the use of the songs of indonesian struggle in particular. Â One of the important aspects in this writing is the function of the song of Indonesian struggle which is divided in one part, firsly, constructive function of the song for ceremonies include advice of the development. The ceremonial character are shown in the song of âIndonesia Rayaâ, the national anthem.